The Antiviral Effect of Novel Steroidal Derivatives on Flaviviruses - Zhang, Luping; Zhou, Dengyuan; Li, Qiuyan; Zhu, Shuo; Imran, Muhammad; Duan, Hongyu; Cao, Shengbo; Ke, Shaoyong; Ye, Jing (Frontiers in Microbiology, 2021)
Flaviviruses are considered to be major emerging arthropod-borne pathogens globally. Currently effective anti-ﬂavivirus approaches are still unavailable, thus there is an urgent need for broad-spectrum drugs that can be active against existing and emerging ﬂaviviruses. In this study, the antiviral activity of steroidal dehydroepiandrosterone (DHEA) and 23 synthetic derivatives against flaviviruses such as Japanese encephalitis virus (JEV), Dengue virus (DENV), and Zika virus (ZIKV) were evaluated by measuring the hallmark features of virus replication both in vitro and in vivo. Our results revealed that AV1003, AV1004 and AV1017 were potent inhibitors of flavivirus multiplication in cells and mainly blocked the post-attachment stage of viral infection. Those three DHEA analogues exhibited the best inhibitory effects against flaviviruses in a dose-dependent manner. Furthermore, orally administered compound AV1004 protected mice from lethal JEV infection by reducing the viral titers in the brain and promoting survival of infected mice. These results indicate that the compound AV1004 might be a feasible therapeutic agent against JEV infection and these DHEA derivatives may provide promising lead scaffolds for the further design and synthesis of potential antiviral agents.